The Effect of Multimedia Assisted Scientific Learning Strategies and Scientific Attitudes on Critical Thinking Ability in Class IV Elementary School Students in IPA - Dwi Putamayanti; Happy Karlina Marjo; Amalia Sapriati (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of the interaction of the application of multimedia-assisted scientific learning and scientific attitudes on the critical thinking skills of fourth grade elementary school students in science subjects. The study used a quasi-experimental method with a 2 x 2 factorial design, with a population of 60 students and a sample of 30 students in class IV. The research instrument is in the form of tests and questionnaires that have been tested and tested for validity and reliability. After being given treatment to the two experimental classes, the results obtained (1) there is a difference between the application of multimedia-assisted scientific learning strategies and scientific learning strategies without multimedia significantly on the critical thinking skills of fourth grade elementary school students, namely 79.17 and 70, respectively. 73. (2) there is a difference between high scientific attitude and low scientific attitude towards students' critical thinking skills in elementary schools, namely 81.46 and 69.91. (3) there is an interaction between scientific learning strategies and scientific attitudes towards students' critical thinking skills, which is 0.033. The conclusion of this research is that there is an interaction between multimedia-assisted scientific learning strategies and scientific attitudes towards critical thinking of elementary school students in science subjects.